C-Cl activation of the weakly coordinating anion [B(3,5-Cl2C6H3)4]- at a Rh(I) centre in solution and the solid-state. - Pike, S; Weller, A (2013)
Addition of H2 to [Rh((i)Bu2PCH2CH2P(i)Bu2)(NBD)][BAr(Cl)4] (NBD = norbornadiene, Ar(Cl) = 3,5-Cl2C6H3) in the solid-state results in the rapid formation of zwitterionic [Rh((i)Bu2PCH2CH2P(i)Bu2){(η(6)-C6H3Cl2)BAr(Cl)3}] by a gas/solid reaction. This undergoes slow C-Cl bond cleavage in the solid-state to ultimately afford the dimeric Rh(III) complex [RhCl((i)Bu2PCH2CH2P(i)Bu2){C6H3Cl(BAr(Cl)3)}]2. This reactivity is mirrored in solution (CH2Cl2). Kinetic data for the C-Cl activation in both the solid-state and solution are reported.